Compliance with infection control practices in an university hospital dental clinic - Mutters, Nico T.; Hägele, Ulrike; Hagenfeld, Daniel; Hellwig, Elmar; Frank, Uwe (German Medical Science GMS Publishing House, 2014)
[english] Aim: Compliance with infection control practices is the key to quality care and excellence in dentistry. Infection control remains one of the most cost-beneficial interventions available. However, implementing control procedures requires full compliance of the whole dental team. The aim of our study was to measure the compliance in daily clinical practice.Methods: The compliance with infection control practices in dentistry by dental health care personnel (DHCP) in a German university dental clinic was observed during clinical work. In addition, a survey was conducted to assess the individual knowledge about infection control procedures. Contamination of the workplace during invasive dental procedures was tested, as well.Results: A total of 58 invasive dental treatments implying close contacts between HCWs and patients were scrutinized. All HCWs (100%) wore gloves during dental work, but in some cases (female dentists: 14.3%; dental assistants: 28.6%) gloves were neither changed nor hands were disinfected between different activities or patient contacts (female dentists: 68.6%; male dentists: 60.9%; dental assistants: 93%). Only 31.4% of female and 39.1% of male dentists carried out adequate hygienic hand disinfection after removing gloves. Male dentists wore significantly more often (100%) protective eyewear compared to 77.1% of female dentists (p<0.05). In addition, most of female dentists (62.9%) and dental assistants (80.7%) wore jewelry during dental procedures. Conclusion: Despite the knowledge of distinct hygiene procedures only a small percentage of dental staff performs hygiene practices according to recommended guidelines. Strict audit is clearly needed in the dental setting to ensure compliance with infection control guidelines to prevent transmission of pathogens. Our results provide insights for the development of a targeted education and training strategy to enhance compliance of dental staff especially of dental assistants with infection control procedures.